Influence of rural clinical school experience and rural origin on practising in rural communities five and eight years after graduation. Issue 11 (1st April 2022) - Seal, Alexa N; Playford, Denese; McGrail, Matthew R; Fuller, Lara; Allen, Penny L; Burrows, Julie M; Wright, Julian R; Bain‐Donohue, Suzanne; Garne, David; Major, Laura G; Luscombe, Georgina M
Abstract: Objective: To examine associations between extended medical graduates' rural clinical school (RCS) experience and geographic origins with practising in rural communities five and eight years after graduation. Design, participants: Cohort study of 2011 domestic medical graduates from ten Australian medical schools with rural clinical or regional medical schools. Main outcome measures: Practice location types eight years after graduation (2019/2020) as recorded by the Australian Health Practitioner Regulation Agency, classified as rural or metropolitan according to the 2015 Modified Monash Model; changes in practice location type between postgraduate years 5 (2016/2017) and 8 (2019/2020). Results: Data were available for 1321 graduates from ten universities; 696 were women (52.7%), 259 had rural backgrounds (19.6%), and 413 had extended RCS experience (31.3%). Eight years after graduation, rural origin graduates with extended RCS experience were more likely than metropolitan origin graduates without this experience to practise in regional (relative risk [RR], 3.6; 95% CI, 1.8–7.1) or rural communities (RR, 4.8; 95% CI, 3.1–7.5). Concordance of location type five and eight years after graduation was 92.6% for metropolitan practice (84 of 1136 graduates had moved to regional/rural practice, 7.4%), 26% for regional practice (56 of 95 had moved to metropolitan practice, 59%), and 73% for rural practice (20 of 100 had moved to metropolitan practice, 20%). Metropolitan origin graduates with extended RCS experience were more likely than those without it to remain in rural practice (RR, 2.0; 95% CI, 1.3–2.9) or to move to rural practice (RR, 1.9; 95% CI, 1.2–3.1). Conclusion: The distribution of graduates by practice location type was similar five and eight years after graduation. Recruitment to and retention in rural practice were higher among graduates with extended RCS experience. Our findings reinforce the importance of longitudinal rural and regional training pathways, and the role of RCSs, regional training hubs, and the rural generalist training program in coordinating these initiatives.